Greenhouse Modeling, Validation and Climate Control based on Fuzzy Logic - Jomaa, M.; Abbes, M.; Tadeo, F.; Mami, A. (Engineering, Technology & Applied Science Research, 2019)
This paper deals with the modeling and control of the air temperature and humidity in greenhouses. A physical model of the greenhouse used in the Simulink/Matlab environment is elaborated to simulate both temperature and indoor humidity. As a solution to the non-linearity and complexity of the greenhouse system, a fuzzy logic method is developed to control the actuators that are installed inside the greenhouse for heating, ventilation, humidification and cooling to obtain a suitable microclimate.